Rare bird documentation form for Greater Scaup at Lake Manawa, 1981 - Wilson, Barbara L.et al (1981)
Rare bird documentation form for a Greater Scaup at Lake Manawa in Pottawattamie County, IA on April 11, 1981. Epson - sheet feed